Livro Digital Interativo: Um Exemplo com Trigonometria - Araya, Eduardo Alejandro Flores (2021)
The present work consists in the creation of an interactive digital book using the Descartes NIPPES (Núcleo Interactivo para Programas Educativos – Interactive Core for Educational Software). In order to do this, we decided to do a trigonometry example, since it is one of the hardest topics to learn. The book is composed in HTML5 format, it is multi-platform and it can be accessed both online and offline. The book template was developed by the iCartesiLibris project using CCS. The aim of this work is to present a tool unknown in Brazil, to motivate teachers more than in a mere presentation, but using informational technologies, since this interactive material can solidly assist in the learning process of the students in the newest educative realities that have emerged throughout all educational levels, especially during pandemics times.